2013
DOI: 10.5032/jae.2013.03001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Time Management Professional Development Seminar on Stress and Job Satisfaction of Beginning Agriscience Teachers in West Texas

Abstract: The purpose of this study was to determine the effects of a time management seminar on stress and job satisfaction of beginning agriscience teachers.The target population for this study consisted of agriscience teachers in the first or second year of tenure. All twenty-three (N = 23) beginning teachers from a selected region of the state participated in the study. There was a 100% response. Eleven participated in the time management seminar (n = 11) and 12 participated in the control group (n = 12). The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…This is consistent with previous research findings that agriculture teachers are generally satisfied with their jobs (Bennett et al, 2002;Cano & Miller, 1992;Castillo et al, 1999;Chenevey et al, 2008;Grady & Burnett, 1985;Kitchel et al, 2012;Ritz et al, 2013;Walker et al, 2004). We found job satisfaction was significantly correlated with professional commitment.…”
Section: Conclusion Implications and Recommendationssupporting
confidence: 82%
“…This is consistent with previous research findings that agriculture teachers are generally satisfied with their jobs (Bennett et al, 2002;Cano & Miller, 1992;Castillo et al, 1999;Chenevey et al, 2008;Grady & Burnett, 1985;Kitchel et al, 2012;Ritz et al, 2013;Walker et al, 2004). We found job satisfaction was significantly correlated with professional commitment.…”
Section: Conclusion Implications and Recommendationssupporting
confidence: 82%
“…TSI is an instrument to identify the stress source and its manifestation towards the stress. The domains in the instrument are Professional Investment, Time Management, Work-related Stressors, Discipline and Motivation, Professional Stress, Behavioral Manifestations as extended stress manifestation (Ritz, 2009& Olivier, 2003. Domains of Manifestation towards stress are Emotional Manifestations, Gastronomical Manifestations, Cardiovascular Manifestations, and Fatigue Manifestations (Ritz, 2009& Olivier, 2003.…”
Section: Methodsmentioning
confidence: 99%
“…Studies reviewed by Siddiqui (2012) in Hyberdad city, Ritz, Burris, Brashears and Fraze (2013) and Ngari, et al (2013) in Kenya have shown that teachers experience moderate to high levels of stress. The studies reviewed cut across countries of the world from underdeveloped, developing and developed countries.…”
Section: Wwwgjournalsorg 57mentioning
confidence: 99%
“…It is not clear on whether the study addressed all the teachers from pre-school to the university level. Ritz, Burris, Brashears and Fraze (2013) on the other hand in their study on the effects of a time management professional development seminar on stress and job satisfaction of beginning Agri-science teachers in West Texas, found out that the beginning teachers had slight to moderate stress. Additionally, the teachers had slightly above neutral levels of job satisfaction.…”
Section: Synthesis Of Literature On Levels Of Stressmentioning
confidence: 99%
See 1 more Smart Citation